Research on Activation Path of Intangible Cultural Heritage Tourism in Qingshen County Based on RMP Analysis - Tang, Yourou (Education Insights, 2026)
Taking Qingshen County, Meishan City as the research object, this paper adopts the RMP analysis model to conduct a systematic analysis of the tourism development of intangible cultural heritage (ICH) in Qingshen County from three dimensions: Resource (R), Market (M) and Product (P). The research finds that Qingshen County is rich in ICH resources, boasting 40 national, provincial, municipal and county-level ICH projects including Qingshen Bamboo Weaving, as well as 67 inheritors. It integrates diverse cultures such as Cancong Culture and Dongpo Culture, and has a sound ecological foundation. However, there exist several problems, such as the limited influence of ICH tourism, a single source of tourists, and insufficient depth of product experience. Based on the resource evaluation of "scarcity-inheritance-experience" and the consumption preference data of target customer groups, this paper constructs an activation path for the precise matching of "resources-markets-products", aiming to promote the inheritance of ICH and the sustainable development of tourism in Qingshen County.